THE IMPACT OF ACCREDITATION ON PERCEIVED SERVICE QUALITY IN EDUCATIONAL INSTITUTIONS: A STRATEGIC PERSPECTIVE - Husna, Fatimatul; Holifah (International Journal of Multidisciplinary Reseach, 2025)
This study examines how accreditation affects perceived service quality in schools, specifically looking at the strategy at SMP Nurul Jadid. In today's era, accreditation is essential to build public trust in educational institutions. We used a qualitative case study method, collecting data from observations, in-depth interviews with principals, teachers, students, and parents, and reviewing official documents. The main results of this study indicate that